2016
DOI: 10.3847/0004-637x/822/1/44
|View full text |Cite
|
Sign up to set email alerts
|

The Hubble Space Telescope Uv Legacy Survey of Galactic Globular Clusters. Vii. Implications From the Nearly Universal Nature of Horizontal Branch Discontinuities*

Abstract: The UV-initiative Hubble Space Telescope Treasury survey of Galactic globular clusters provides a new window into the phenomena that shape the morphological features of the horizontal branch (HB). Using this large and homogeneous catalog of UV and blue photometry, we demonstrate that the HB exhibits discontinuities that are remarkably consistent in color (effective temperature). This consistency is apparent even among some of the most massive clusters hosting multiple distinct sub-populations (such as NGC 2808… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 92 publications
2
67
0
Order By: Relevance
“…However, the Balmer jump in these red stars is not significantly stronger than that in the Figure 1. WFC3 photometry (black points) of HB stars in ω Cen (Bellini et al 2017a), shown as a color-color diagram that makes it easy to discern the G-jump and M-jump (labeled; as in Brown et al 2016). The ordinate is a color index (C) that is useful for discerning changes in the stellar atmosphere (in the hot stars here but also the cooler stars studied in the multiple populations phenomenon).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the Balmer jump in these red stars is not significantly stronger than that in the Figure 1. WFC3 photometry (black points) of HB stars in ω Cen (Bellini et al 2017a), shown as a color-color diagram that makes it easy to discern the G-jump and M-jump (labeled; as in Brown et al 2016). The ordinate is a color index (C) that is useful for discerning changes in the stellar atmosphere (in the hot stars here but also the cooler stars studied in the multiple populations phenomenon).…”
Section: Discussionmentioning
confidence: 99%
“…For our investigation, we obtained STIS near-UV (G230L) and blue (G430L) spectroscopy of six stars (colored symbols matching those in Figure 2) that straddle the M-jump, with wavelength coverage that includes the three photometric bands employed in this color-color diagram (F275W, F336W, and F438W). If the photometry here is aligned to a theoretical zero-age HB locus (see Brown et al 2016), the gray band representing the M-jump spans ∼15,000-18,000 K in effective temperature. Decl.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations